A new compound heterozygous CFTR mutation in a Chinese family with cystic fibrosis. (3rd November 2015) - Xie, Yingjun; Huang, Xueqiong; Liang, Yujian; Xu, Lingling; Pei, Yuxin; Cheng, Yucai; Zhang, Lidan; Tang, Wen
Abstract: Introduction: Cystic fibrosis (CF) is the most common autosomal recessive disease among Caucasians but is rarer in the Chinese population, because mutations in the cystic fibrosis transmembrane conductance regulator ( CFTR ) gene. Objectives: To elucidate the causative role of a novel compound heterozygous mutation of CF. Materials and Methods: In this study, clinical samples were obtained from two siblings with recurrent airway infections, clubbed fingers, salt‐sweat and failure to gain weight in a non‐consanguineous Chinese family. Next‐generation sequencing was performed on the 27 coding exons of CFTR in both children, with confirmation by Sanger sequencing. Results: Next‐generation sequencing showed the same compound heterozygous CFTR mutation ( c.865A>T p.Arg289X and c.3651_3652insAAAT p.Tyr1219X ) in both children. Conclusions: As this mutation is consistent with the clinical manifestations of CF and no other mutations were detected after scanning the gene sequence, we suggest that the CF phenotype is caused by compound heterozygosity for c.865A>T and c.3651_3652insAAAT . As c865A > T is not currently listed in the "Cystic Fibrosis Mutation Database", this information about CF in a Chinese population is of interest.